2008
DOI: 10.1038/nri2417
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian glycosylation in immunity

Abstract: Glycosylation produces a diverse and abundant repertoire of glycans, which are collectively known as the glycome. Glycans are one of the four fundamental macromolecular components of all cells, and are highly regulated in the immune system. Their diversity reflects their multiple biological functions that encompass ligands for proteinaceous of receptors known as lectins. Since the discovery that selectins and their glycan ligands are important for the regulation of leukocyte trafficking, it has been shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
519
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 606 publications
(526 citation statements)
references
References 180 publications
2
519
1
4
Order By: Relevance
“…The precise glycan structures present on a mature protein can influence protein function in a variety of ways and are important in processes including infection, immunity, cancer, and development. [8][9][10][11] Diversification and regulation of OTase activity seems to have occurred by various mechanisms throughout evolution. Organisms including some Nglycosylating bacteria and divergent eukaryotes have multiple single subunit OTase enzymes homologous to the catalytic Stt3p protein.…”
Section: Introductionmentioning
confidence: 99%
“…The precise glycan structures present on a mature protein can influence protein function in a variety of ways and are important in processes including infection, immunity, cancer, and development. [8][9][10][11] Diversification and regulation of OTase activity seems to have occurred by various mechanisms throughout evolution. Organisms including some Nglycosylating bacteria and divergent eukaryotes have multiple single subunit OTase enzymes homologous to the catalytic Stt3p protein.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been demonstrated that a diverse range of bacterial chitinases hydrolyse GlcNAc-containing model substrates of LacdiNAc and to a lesser extent also LacNAc, though at low rates (Larsen et al, 2011;Murata et (Varki et al, 2009), and are abundant in proteins of the human immune system (Marth & Grewal, 2008). The possibility that bacteria might be using LacNac structures in O-glycans as substrates has been proposed for a commensal of the human gut, Bacteroides thetaiotaomicron (Martens et al, 2008).…”
Section: Substrate Specificities Of Catalytic Domains Relevant To Virmentioning
confidence: 99%
“…More moderate physiological and pathophysiological changes in immune cell function occur during aging, but also in autoimmunity and cancer. One mechanism to alter immune cell function arises from the degree and pattern of glycosylation in immune cells (19,20). Although many immune cell surface receptors show complex glycosylation patterns, one alternative target to affect immune cell function by changes in glycosylation may involve altering proteins that regulate SOCE.…”
mentioning
confidence: 99%